Addressing asymmetry of the charge and strain in a two-dimensional fullerene peapod. Issue 2 (11th December 2015) - Valeš, V.; Verhagen, T.; Vejpravová, J.; Frank, O.; Kalbáč, M.
Abstract : Correlation of the local changes in strain and doping with local roughness in a two-dimensional fullerene peapod. Abstract : We prepared a two-dimensional C70 fullerene peapod by the sequential assembly of 12 C graphene, C70 fullerenes and 13 C graphene. The local changes in the strain and doping were correlated with local roughness revealing asymmetry in the strain and doping with respect to the top and bottom graphene layers of the peapod.